INFLATION IN LIBYA - منصور, حسام الدين (Dirasat in Economics and Business, 1968)
Inflation defined as a continuous rise in the general price level should be distinguished from seasonal variation in the price level and changes in the relative prices of commodities whatever the reason for this change may be. The rise in prices of goods and services during inflation is not restricted to goods and servies produced locally but also extends to goods and services crossing the national frontiers due to a rise in the foreign exchange rate if the country in question is adopting a free and fluctuating exchange rate or due to difficulties in its balance of payment if it adheres to fixed exchange rate. There is dearth of statistical figures as far as price indeces are concerned in Libya and the figures that are available do not indicate a sharp rise in the local prices ; thus while the quantity of money in circulation has risen by eleven times from 1957 to 1967, the retail price index of the principal food commadities has risen by about 63%. The wide discrepency between the rise in quantity of money & the reported figures on price indeces, I believe is due to the following factors : (1) The rise in income has induced a rise in the quantity of money held by the private sector, i.e. a fall in the income velocity of circulation of money ; (2) The rise in the quantity of money during this period was due to a favorable balance on the capital and current account of the balance of payment and not due to local credit expansion or the printing press method of increase_ions that ing the supply of money. The country has never used locall.. the capital resources available to it; (3) part of the increas quantity of money may have been used to finance transactions were financed previously on a barter basis. The rise in the general price level is an accepted fact as far as the average person in the country is concerned ; however there is no reason to infere that this rise constitute more than a case of disquilibrum in the market due to shift in the demand function brought about primarily by a rise in the real income. The rise in the real income itself was a result of growth in the production of goods and services that is not directly suitable for consumption ; thus the relative inelasticity of the supply of the various consumer products caused a rise in the general price level in the country, but had the rise in the real income been the result of a rise in the supply of consumption goods, prices would have remained relatively stable. In a market economy every supply is elastic in the long run, therefore sooner or later the aggregate supply of goods and services will respond to the increase in demand and the rise in prices will find a limit providing that the monetary and fiseal authorities are not behaving in a manner that will produce a deficit on the balance of payment and there by causing a deterioration in the position of the Libyan pound. A rise in the price level such as happened in Libya is necessary in order to allow the market forces to get momentum and reestablish equilibruim again.